Interfacial Softening and Electrolyte Uptake in Co3O4 OER Catalysts: Insight from Operando Spectroscopy and Fast EQCM‐D - Leppin, Christian; Placke‐Yan, Carsten; Bendt, Georg; Hernandez, Sheila; Tschulik, Kristina; Schulz, Stephan; Linnemann, Julia (ChemCatChem)
Cobalt spinel (Co3O4) catalysts are widely studied in scope of the electrocatalytic oxygen evolution reaction (OER), yet the role of interfacial structural transformation under anodic bias remains under debate. Here, we employ an operando approach, combining a fast electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D), electrochemical impedance spectroscopy (EIS), and Raman spectroscopy to investigate interfacial transformations of Co3O4 nanoparticle electrodes in alkaline electrolyte. We identify two distinct regimes during the anodic sweep prior to the macroscopic OER onset. At lower potentials, the catalyst interface remains mechanically rigid while reversibly associating several OH−/H2O species per oxidized cobalt site. At higher potentials, pronounced softening of the interface occurs alongside further uptake of electrolyte species. This indicates amorphization and a ‘swelling process’ beyond simple adsorption. Notably, an electrochemical conditioning treatment can suppress mass and compliance hysteresis without affecting OER activity, suggesting that most incorporated electrolyte species do not participate in the OER. EIS further reveals that OER intermediates form well below the apparent OER onset potential. These results advance our mechanistic understanding of interfacial transformations in cobalt-based OER catalysts and establish EQCM-D as a sensitive operando technique for probing electrocatalyst transformations.
Keywords: electrocatalysis; Co3O4; EQCM-D; OER

Role of Defects in Reversible Surface Restructuring and Activity of Co3O4 Oxygen Evolution Electrocatalysts - Scharf, Carl Hendric; Chandraraj, Alex; Dyk, Konrad; Stebner, Felix; Lepin, Sören; Tian, Jing; El Bergmi Byaz, Laila; Stettner, Jochim; Leppin, Christian; Kotova, Anastasiia; Reinke, Sebastian; Linnemann, Julia; et al. (ACS Catalysis)
Overcoming the slow kinetics of the oxygen evolution reaction at the anode is a key challenge for the production of hydrogen via electrolysis. This reaction operates at very positive potentials, where the electrocatalyst is exposed to highly oxidative conditions and prone to potential-dependent transformation of the near-surface region. While substantial evidence for such surface restructuring exists, its extent and relevance for the catalyst’s activity are unclear. We address this topic for the case of Co3O4, one of the best-known electrocatalysts exhibiting surface restructuring, by studies of epitaxial (111)-ordered electrodeposited films with combined operando X-ray surface diffraction and absorption spectroscopy, electrochemical impedance spectroscopy, and electrochemical measurements on rotating disk electrodes. Comparison of the as-prepared and annealed state of the same samples, which both are stable even under long-term oxygen evolution conditions, provides clear insight into the role of surface defects. Our results show that defect-free annealed Co3O4(111) surfaces are structurally stable over a wide potential range and hydroxylate via adsorption at surface oxygen and Co sites. Potential-induced surface restructuring of the Co3O4 lattice occurs only in the presence of surface defects, leading to the formation of the well-known nanometer-thick oxyhydroxide skin layer. The presence of this skin layer promotes oxygen evolution at low overpotentials but results in higher Tafel slopes. As a result, highly ordered Co3O4(111) surfaces are more active at high current densities than defective Co3O4 surfaces that undergo surface restructuring. These results highlight that strategies for catalyst surface defect engineering need to be application-oriented.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization

The catalyst that stores charge first - Linnemann, Julia; Leppin, Christian (Bunsen-Magazin)
Alkaline oxygen evolution on Co3O4 involves more than adsorption and electron transfer at a fixed surface. The article draws on operando electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D), surface X-ray diffraction (SXRD), Raman, UV/Vis and impedance spectroscopy. On this basis, it discusses pseudocapacitive oxidation of cobalt ion sites, electrolyte uptake and near-surface transformation, and asks which of these changes are kinetically coupled to electrocatalysis.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization; spectroelectrochemistry

Complementary Analysis of Cyclic Voltammograms and Impedance Spectra of Porous Carbon Electrodes - Reinke, Sebastian; Khamitsevich, Vera; Linnemann, Julia (2024 International Workshop on Impedance Spectroscopy (IWIS))
Porous carbons are prominent electrode materials in energy storage applications such as supercapacitors. However, rational materials development is hampered by difficulties in interpreting electrochemical impedance spectra (EIS) and drawing conclusions about promising aspects of device improvement. Here, we characterized electrodes consisting of activated carbon with polyacrylic acid binder in four different concentrations of sulfuric acid, using cyclic voltammetry and electrochemical impedance spectroscopy. Both datasets were evaluated with simple equivalent circuits and comparatively analyzed. Conductivity of the electrolyte was independently measured. Cyclic voltammograms (CV) show larger resistance and capacitance at low scan rates. Resistances obtained from EIS are in good agreement with those obtained by cyclic voltammograms particularly at high scan rates. The comparison against specific electrolyte resistance can reveal whether resistances within the solid electrode architecture or resistances within the electrolyte, partially confined by pores, are the dominant cause of increased resistance at low scan rate. Comparison between CV and EIS points to the main electrode capacitance being described by a constant phase element (CPE) used to fit the low-frequency region of EIS.
Keywords: electrochemical impedance spectroscopy; distorted cyclic voltammograms; supercapacitors; carbon

Morphological Degradation of Oxygen Evolution Reaction-Electrocatalyzing Nickel Selenides at Industrially Relevant Current Densities - Hiege, Felix; Chang, Chun-Wai; Trost, Oliver; van Halteren, Charlotte E. R.; Hosseini, Pouya; Bendt, Georg; Schulz, Stephan; Feng, Zhenxing; Linnemann, Julia; Tschulik, Kristina (ACS Applied Materials & Interfaces)
We investigated electrodeposited nanoparticulate nickel selenide (pre)catalysts that transform into nickel oxides/oxyhydroxides under oxygen evolution reaction conditions in alkaline solutions. Previous studies of this transformation were conducted at lower current densities than those of industrial relevance (≥1 A cm–2). We used ultramicroelectrodes (UMEs) to achieve such current densities, benefiting from their small size, ensuring low absolute currents and low ohmic drop but high current densities. Morphological degradation of the catalyst material was only observed at current densities exceeding 1 A cm–2 but not for smaller ones. Using X-ray absorption, X-ray photoemission spectroscopy, and X-ray diffraction, we confirmed that the degradation was accompanied by the literature-known transformation of nanoparticulate Ni3Se2 (bulk)/NiSe (surface) into nickel oxyhydroxide. The transformation of the precatalyst goes along with a significant improvement in the charge transfer kinetics observed by decreasing Tafel slopes with ongoing experimental time extracted from cyclic voltammetry (CV) experiments and electrochemical impedance spectroscopy (EIS) in the high-frequency range. However, these kinetic improvements are accompanied by limitations in mass transport concluded from decreasing current responses at high overpotentials in CVs and increasing impedance in the low-frequency range of the EIS spectra after extended CV cycling. These mass transport limitations originated from morphological degradations at the UME exceeding 1 A cm–2 which we proved by applying identical location scanning electron microscopy. This has not been reported in studies that have been limited to lower current densities before. Our findings showcase how UMEs can be used to study (pre)catalysts (herein nickel selenides) under current densities of industrial relevance in the absence of ohmic drop-related ambiguities, combined with in-depth materials characterization studies, e.g., identical location microscopy and advanced spectroscopic methods. This approach enables direct evaluation and comparison of catalyst materials and thus demonstrates how to overcome long-standing limitations of electrocatalyst design and testing.
Keywords: Electrocatalysis; oxygen evolution reaction; nickel selenide; microelectrode

Operando Analysis of the Pre-OER Activation of Metal-Doped Co3O4 Nanoparticle Catalysts - Kampermann, L.; Klein, J.; Wagner, T.; Kotova, A.; Placke-Yan, C.; Yasar, A.; Jacobse, L.; Lasagna, S.; Leppin, Christian; Schulz, S.; Linnemann, Julia; Bergmann, A.; et al. (ACS Catalysis)
Doped Co3O4 nanoparticles are investigated via spectro-electrochemistry in the (pre-) oxygen evolution reaction (OER) regime by tracing the absorption signal of the Co3+ d–d transition under applied bias for getting insight into the catalysts activation and the formation of catalytically active phases. In the low potential regime up to 1.37 VRHE, a rise in the optical absorption signal of the [Co3+]oct d–d transition is observed and attributed to a structural change from [Co2+]tet to [Co3+]oct due to an electrochemically induced surface restructuring with water. For applied potentials higher than 1.37 VRHE an overall offset of the absorption spectra in the UV–vis range, equivalent to a darkening of the materials is detected. This is attributed to the formation of a CoOx(OH)y skin layer as supported by high-energy X-ray diffraction (HE-XRD) measurements. We found that the kinetics of the Co3+ states are heavily influenced by the type of dopant with V-doped Co3O4 exhibiting stable Co3+ states (>20 min) while the Mn-doped Co3O4 Co3+ states reduce within 36 s under reductive bias. We conclude that doping Co3O4 with transition metals affects the formation and potential-dependent thickness of the CoOx(OH)y skin layer as the catalytically active phase and the formation of long-time stable surface Co3+ states after activation in the first OER cycle.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization; spectroelectrochemistry

Assessment of the Physicochemical Meaning of the Ohmic Series Resistance Observed for High Frequencies in Electrochemical Impedance Spectra - Reinke, Sebastian; Khamitsevich, Vera; Röth, Oliver; Linnemann, Julia (2023 International Workshop on Impedance Spectroscopy (IWIS))
Attributing features of electrochemical impedance spectra to electrochemical phenomena is both crucial and frequently ambiguous. To elucidate the origin of the ohmic part of the spectrum, activated carbon electrodes were prepared with different contents of polyacrylic acid as binder. Their impedance spectra and cyclic voltammograms were recorded using sulfuric acid of five different concentrations as the electrolyte. To distinguish electrolyte resistance and resistances related to the activated carbon layer of the electrode, the specific electrolyte conductivity was independently measured and compared against the ohmic part of the electrochemical impedance spectra (EIS). The capacitive cyclic voltammograms show larger resistive contributions with higher scan rate and lower electrolyte conductivity. Comparing the ohmic part of the EIS to the specific resistance of the electrolyte, a linear function with no statistically significant offset was found. The ohmic part of the EIS, thus, reflects the electrolyte resistance, not that of the carbon electrode.
Keywords: electrochemical impedance spectroscopy; supercapacitors; carbon

Tailoring Pore Size and Catalytic Activity in Cobalt Iron Layered Double Hydroxides and Spinels by Microemulsion‐Assisted pH‐Controlled Co‐Precipitation - Rabe, Anna; Jaugstetter, Maximilian; Hiege, Felix; Cosanne, Nicolas; Ortega, Klaus Friedel; Linnemann, Julia; Tschulik, Kristina; Behrens, Malte (ChemSusChem)
Cobalt iron containing layered double hydroxides (LDHs) and spinels are promising catalysts for the electrochemical oxygen evolution reaction (OER). Towards development of better performing catalysts, the precise tuning of mesostructural features such as pore size is desirable, but often hard to achieve. Herein, a computer‐controlled microemulsion‐assisted co‐precipitation (MACP) method at constant pH is established and compared to conventional co‐precipitation. With MACP, the particle growth is limited and through variation of the constant pH during synthesis the pore size of the as‐prepared catalysts is controlled, generating materials for the systematic investigation of confinement effects during OER. At a threshold pore size, overpotential increased significantly. Electrochemical impedance spectroscopy (EIS) indicated a change in OER mechanism, involving the oxygen release step. It is assumed that in smaller pores the critical radius for gas bubble formation is not met and therefore a smaller charge‐transfer resistance is observed for medium frequencies.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; cobalt hydroxide; LDH

3D atomic-scale imaging of mixed Co-Fe spinel oxide nanoparticles during oxygen evolution reaction - Xiang, Weikai; Yang, Nating; Li, Xiaopeng; Linnemann, Julia; Hagemann, Ulrich; Ruediger, Olaf; Heidelmann, Markus; Falk, Tobias; Aramini, Matteo; DeBeer, Serena; Muhler, Martin; Tschulik, Kristina; et al. (Nature Communications)
The three-dimensional (3D) distribution of individual atoms on the surface of catalyst nanoparticles plays a vital role in their activity and stability. Optimising the performance of electrocatalysts requires atomic-scale information, but it is difficult to obtain. Here, we use atom probe tomography to elucidate the 3D structure of 10 nm sized Co2FeO4 and CoFe2O4 nanoparticles during oxygen evolution reaction (OER). We reveal nanoscale spinodal decomposition in pristine Co2FeO4. The interfaces of Co-rich and Fe-rich nanodomains of Co2FeO4 become trapping sites for hydroxyl groups, contributing to a higher OER activity compared to that of CoFe2O4. However, the activity of Co2FeO4 drops considerably due to concurrent irreversible transformation towards CoIVO2 and pronounced Fe dissolution. In contrast, there is negligible elemental redistribution for CoFe2O4 after OER, except for surface structural transformation towards (FeIII, CoIII)2O3. Overall, our study provides a unique 3D compositional distribution of mixed Co-Fe spinel oxides, which gives atomic-scale insights into active sites and the deactivation of electrocatalysts during OER.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; electrochemical impedance spectroscopy

Mechanism of coupled phase/morphology transformation of 2D manganese oxides through Fe galvanic exchange reaction - Aymerich-Armengol, Raquel; Cignoni, Paolo; Ebbinghaus, Petra; Linnemann, Julia; Rabe, Martin; Tschulik, Kristina; Scheu, Christina; Lim, Joohyun (Journal of Materials Chemistry A)
Nanostructured manganese oxides have a rich variety of morphologies and crystal phases which can undergo transformations during synthesis and application. Although these structural features are crucial for their performance, the mechanisms behind such transitions are not well understood. Herein, we describe the mechanism of transformation from layered 2D δ-MnO2 nanosheets to the scarcely reported γ-MnO2 nanocone morphology. Despite the common purpose of introducing Fe dopants to enhance the conductivity of layered manganese oxides, the Fe galvanic exchange reaction was found responsible for such coupled phase/morphology transition. Electrochemical characterization confirmed a distinct electrochemical behaviour of the nanocones, emphasizing the need to unravel the mechanism of 2D MnO2 transformation. Such mechanistic insights were gained by systematic and rigorous electron microscopy studies. The effect of the local chemical composition was determined by energy dispersive X-ray spectroscopy while electron energy loss spectroscopy unravelled the key influence of the oxidation state of Mn ions within nanosheets and nanocones. We propose and demonstrate a Mn2+-mediated oxidative mechanism of coupled morphology/phase transformation subjected to the equilibrium of Fe and Mn ions during galvanic exchange reaction. These findings contribute to the understanding of the growth and morphology/phase transformations of manganese oxide nanostructures, providing insights for the rational design of nanomaterials.
Keywords: manganese oxide; nanomaterials; TEM; supercapacitors

Design Strategies for Electrocatalysts from an Electrochemist’s Perspective - Linnemann, Julia; Kanokkanchana, Kannasoot; Tschulik, Kristina (ACS Catalysis)
The aim to produce highly active, selective, and long-lived electrocatalysts by design drives major research efforts toward gaining fundamental understanding of the relationship between material properties and their catalytic performance. Surface characterization tools enable to assess atomic scale information on the complexity of electrocatalyst materials. Advancing electrochemical methodologies to adequately characterize such systems was less of a research focus point. In this Review, we shed light on the ability to gain fundamental insights into electrocatalysis from a complementary perspective and establish corresponding design strategies. These may rely on adopting the perceptions and models of other subareas of electrochemistry, such as corrosion, battery research, or electrodeposition. Concepts on how to account for and improve mass transport, manage gas bubble release, or exploit magnetic fields are highlighted in this respect. Particular attention is paid to deriving design strategies for nanoelectrocatalysts, which is often impeded, as structural and physical material properties are buried in electrochemical data of whole electrodes or even devices. Thus, a second major approach focuses on overcoming this difference in the considered level of complexity by methods of single-entity electrochemistry. The gained understanding of intrinsic catalyst performance may allow to rationally advance design concepts with increased complexity, such as three-dimensional electrode architectures. Many materials undergo structural changes upon formation of the working catalyst. Accordingly, developing “precatalysts” with low hindrance of the electrochemical transformation to the active catalyst is suggested as a final design strategy.
Keywords: electrocatalysis

Unexpectedly High Capacitance of the Metal Nanoparticle/Water Interface: Molecular‐Level Insights into the Electrical Double Layer - Azimzadeh Sani, Mahnaz; Pavlopoulos, Nicholas G.; Pezzotti, Simone; Serva, Alessandra; Cignoni, Paolo; Linnemann, Julia; Salanne, Mathieu; Gaigeot, Marie‐Pierre; Tschulik, Kristina (Angewandte Chemie International Edition)
The electrical double‐layer plays a key role in important interfacial electrochemical processes from catalysis to energy storage and corrosion. Therefore, understanding its structure is crucial for the progress of sustainable technologies. We extract new physico‐chemical information on the capacitance and structure of the electrical double‐layer of platinum and gold nanoparticles at the molecular level, employing single nanoparticle electrochemistry. The charge storage ability of the solid/liquid interface is larger by one order‐of‐magnitude than predicted by the traditional mean‐field models of the double‐layer such as the Gouy–Chapman–Stern model. Performing molecular dynamics simulations, we investigate the possible relationship between the measured high capacitance and adsorption strength of the water adlayer formed at the metal surface. These insights may launch the active tuning of solid–solvent and solvent–solvent interactions as an innovative design strategy to transform energy technologies towards superior performance and sustainability.
Keywords: single-entity electrochemistry; electrical double layer; supercapacitor; nanoparticles

Single Co3O4 Nanocubes Electrocatalyzing the Oxygen Evolution Reaction: Nano-Impact Insights into Intrinsic Activity and Support Effects - Liu, Zhibin; Corva, Manuel; Amin, Hatem M. A.; Blanc, Niclas; Linnemann, Julia; Tschulik, Kristina (International Journal of Molecular Sciences)
Single-entity electrochemistry allows for assessing electrocatalytic activities of individual material entities such as nanoparticles (NPs). Thus, it becomes possible to consider intrinsic electrochemical properties of nanocatalysts when researching how activity relates to physical and structural material properties. Conversely, conventional electrochemical techniques provide a normalized sum current referring to a huge ensemble of NPs constituting, along with additives (e.g., binders), a complete catalyst-coated electrode. Accordingly, recording electrocatalytic responses of single NPs avoids interferences of ensemble effects and reduces the complexity of electrocatalytic processes, thus enabling detailed description and modelling. Herein, we present insights into the oxygen evolution catalysis at individual cubic Co3O4 NPs impacting microelectrodes of different support materials. Simulating diffusion at supported nanocubes, measured step current signals can be analyzed, providing edge lengths, corresponding size distributions, and interference-free turnover frequencies. The provided nano-impact investigation of (electro-)catalyst-support effects contradicts assumptions on a low number of highly active sites.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; single-entity electrochemistry

Metal-based nanostructured materials for advanced lithium–sulfur batteries - Balach, Juan; Linnemann, Julia; Jaumann, Tony; Giebeler, Lars (Journal of Materials Chemistry A)
Since the resurgence of interest in lithium–sulfur (Li–S) batteries at the end of the 2000s, research in the field has grown rapidly. Li–S batteries hold great promise as the upcoming post-lithium-ion batteries owing to their notably high theoretical specific energy density of 2600 W h kg−1, nearly five-fold larger than that of current lithium-ion batteries. However, one of their major technical problems is found in the shuttling of soluble polysulfides between the electrodes, resulting in rapid capacity fading and poor cycling stability. This review spotlights the foremost findings and the recent progress in enhancing the electrochemical performance of Li–S batteries by using nanoscaled metal compounds and metals. Based on an overview of reported functional metal-based materials and their specific employment in certain parts of Li–S batteries, the underlying mechanisms of enhanced adsorption and improved reaction kinetics are critically discussed involving both experimental and computational research findings. Thus, material design principles and possible interdisciplinary research approaches providing the chance to jointly advance with related fields such as electrocatalysis are identified. Particularly, we elucidate additives, sulfur hosts, current collectors and functional interlayers/hybrid separators containing metal oxides, hydroxides and sulfides as well as metal–organic frameworks, bare metal and further metal nitrides, metal carbides and MXenes. Throughout this review article, we emphasize the close relationship between the intrinsic properties of metal-based nanostructured materials, the (electro)chemical interaction with lithium (poly)sulfides and the subsequent effect on the battery performance. Concluding the review, prospects for the future development of practical Li–S batteries with metal-based nanomaterials are discussed.
Keywords: lithium-sulfur battery

Electrodeposited metal-organic framework films as self-assembled hierarchically superstructured supports for stable omniphobic surface coatings - Sablowski, Jakob; Linnemann, Julia; Hempel, Simone; Hoffmann, Volker; Unz, Simon; Beckmann, Michael; Giebeler, Lars (Scientific Reports)
Superhierarchically rough films are rapidly synthesised on metal substrates via electrochemically triggered self-assembly of meso/macroporous-structured metal-organic framework (MOF) crystals. These coatings are applied to immobilise a functional oil with low surface energy to provide stable coatings repellent to a wide range of hydrophobic as well as hydrophilic fluids. Such omniphobic surfaces are highly interesting for several applications such as anti-fouling, anti-icing, and dropwise condensation, and become easily scalable with the presented bottom-up fabrication approach. As investigated by environmental scanning electron microscopy (ESEM), the presented perfluorinated oil-infused Cu-BTC coating constitutes of a flat liquid-covered surface with protruding edges of octahedral superstructured MOF crystals. Water and non-polar diiodomethane droplets form considerably high contact angles and even low-surface-tension fluids, e.g. acetone, form droplets on the infused coating. The repellent properties towards the test fluids do not change upon extended water spraying in contrast to oil-infused porous copper oxide or native copper surfaces. It is discussed in detail, how the presented electrodeposited MOF films grow and provide a proficient surface morphology to stabilise the functional oil film due to hemiwicking.
Keywords: electrodeposition; metal-organic framework; MOF; drop-wise condensation; omniphobic coatings

Electrodeposited films to MOF-derived electrochemical energy storage electrodes: a concept of simplified additive-free electrode processing for self-standing, ready-to-use materials - Linnemann, Julia; Taudien, Laura; Klose, Markus; Giebeler, Lars (Journal of Materials Chemistry A)
The thermolysis of electrodeposited metal–organic framework (MOF) films represents a novel approach to build supercapacitor electrodes of already electrically contacted MOF-derived high-performance metal oxide/carbon materials which are also highly interesting for other applications. MOFs are widely utilised as precursors to synthesise functional materials by thermal decomposition (pyrolysis, carbonisation). Using electrochemically coated MOF precursor films instead of powder greatly simplifies the processing of such materials and potentially enhances the resulting active materials' performance. In the case of electrochemical energy storage electrodes, the coated substrate later functions as current collector which is well-attached to the active material without the need for any additives. This close connection decreases electron transfer resistances and saves multiple steps of powder formulation and coating. Films of a metal–organic framework based on 1,3,5-benzene-tricarboxylate (BTC) and cobalt(II) cations were electrochemically coated on cobalt foils which act as the Co2+ cation source. Manganese films were electrodeposited and subsequently partly redissolved in a linker-containing electrolyte to achieve Mn/Mn–BTC bilayered films on stainless steel. This procedure extends the method for any kind of current collector material. The films were thermolysed to gain nanostructured metal oxide spinel (Me3O4)/carbon hybrid electrodes. Investigations of the electrochemical properties in regard to supercapacitor applications show that Co3O4/C films exhibit pseudocapacitance and that Mn3O4/C films are suitable for redox electrodes with high-rate capability operating in a wide potential range in aqueous electrolytes. Co–BTC powder was also thermally treated yielding cobalt particles embedded in a graphitic carbon matrix. The pseudocapacitive properties of conventionally coated films of this powder material are limited.
Keywords: electrodeposition; metal-organic framework; MOF; supercapacitors

Softwood Lignin as a Sustainable Feedstock for Porous Carbons as Active Material for Supercapacitors Using an Ionic Liquid Electrolyte - Klose, Markus; Reinhold, Romy; Logsch, Florian; Wolke, Florian; Linnemann, Julia; Stoeck, Ulrich; Oswald, Steffen; Uhlemann, Martin; Balach, Juan; Markowski, Jens; Ay, Peter; Giebeler, Lars (ACS Sustainable Chemistry & Engineering)
We report on the facile synthesis of porous carbons based on a biopolymer lignin employing a two-step process which includes the activation by KOH in various amounts under an inert gas atmosphere. The resulting carbons are characterized with regard to their structural properties and their electrochemical performance as an active material in double-layer capacitors using for the first time an ionic liquid (EMIBF4) as the electrolyte for this type of carbon material to enhance storage ability. A capacitance of more than 200 F g–1 at 10 A g–1 is achieved for a carbon with a specific surface area of more than 1800 m2 g–1. One of the most crucial factors determining the electrochemical response of the active materials was found to be the strong surface functionalization by oxygen-containing groups. Furthermore, the sulfur content of the carbon precursor lignin does not result in a significant amount of sulfur-containing surface functionalities which might interact with the electrolyte.
Keywords: supercapacitor; carbon; pyrolysis; lignin

A simple one step process for enhancement of titanium foil dye sensitised solar cell anodes - Linnemann, Julia; Giorgio, J.; Wagner, K.; Mathieson, G.; Wallace, G. G.; Officer, D. L. (Journal of Materials Chemistry A)
The photo-conversion efficiency and stability of back-illuminated dye sensitised solar cells with titanium foil based photoanodes are enhanced by a simple nitric acid treatment through which the foil is passivated. This treatment changes the morphology of the titanium foil and increases its electrochemical double layer capacitance.
Keywords: dye sensitized solar cells; DSSCs

Capacitance performance of cobalt hydroxide-based capacitors with utilization of near-neutral electrolytes - Fedorov, Fedor S.; Linnemann, Julia; Tschulik, Kristina; Giebeler, Lars; Uhlemann, Margitta; Gebert, Annett (Electrochimica Acta)
Conventional alkaline solutions used for capacitive performance of electrodeposited cobalt hydroxides have a number of disadvantages as they are corrosive, environmentally unfriendly and provide a small working potential range. In this study, the capacitive properties of electrodeposited cobalt hydroxide/oxide were investigated in 1 M Na2SO4 solution with pH 5.5 by means of cyclic voltammetry, galvanostatic charging/discharging experiments and electrochemical impedance spectroscopy. The capacitance of the cobalt hydroxide/oxide was demonstrated to have high values of 141 F g−1 at scan rate 8 mV s−1 in this 1 M Na2SO4 solution. The anodic potential range is extended by 0.8–1.3 V vs. Ag/AgCl. A good cyclic stability and reversibility were observed.
Keywords: electrodeposition; cobalt hydroxide; supercapacitors